2015
DOI: 10.1039/c5ra21148d
|View full text |Cite
|
Sign up to set email alerts
|

Rice husk derived nanosilica supported Cu(ii) complex: an efficient heterogeneous catalyst for oxidation of alcohols using TBHP

Abstract: We have developed a heterogenized catalyst of Cu(ii) complex immobilized onto nanosilica obtained from rice husk (RH), through Schiff-base condensation between 3-aminopropyltriethoxysilane (APTES) functionalized nanosilica and acetamide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Also in the XPS of the reused catalyst (Figure c), a decreased intensity of Cu II was observed, which suggest that Cu II plays an important role in the reaction and is reduced to Cu 0 /Cu I after the reaction cycle. On the basis of these results and literature precedent, mechanism for the oxidation of alcohols and hydrocarbons in the presence of Cr 3+ ‐Cu 0 /LDH was proposed (Scheme ). In the presence of Cr III , Cu 0 undergoes oxidation to Cu I (Cu 0 + Cr III Cu I + Cr II ) and Cu II undergoes reduction to Cu I (Cu II + Cr II Cu I + Cr III ), which is the active species for catalyzing the oxidation reaction.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Also in the XPS of the reused catalyst (Figure c), a decreased intensity of Cu II was observed, which suggest that Cu II plays an important role in the reaction and is reduced to Cu 0 /Cu I after the reaction cycle. On the basis of these results and literature precedent, mechanism for the oxidation of alcohols and hydrocarbons in the presence of Cr 3+ ‐Cu 0 /LDH was proposed (Scheme ). In the presence of Cr III , Cu 0 undergoes oxidation to Cu I (Cu 0 + Cr III Cu I + Cr II ) and Cu II undergoes reduction to Cu I (Cu II + Cr II Cu I + Cr III ), which is the active species for catalyzing the oxidation reaction.…”
Section: Resultsmentioning
confidence: 74%
“…No noticeable conversion was observed, which indicated that the oxidative transformation most likely occurred via radical intermediates. Cu II or Cu I has been reported as the active species in catalyzing the oxidations using TBHP . Since Cu 0 easily undergoes oxidation to Cu I /Cu II , so the presence of these species in the reaction medium was determined by different experiments and XPS analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Since, MeCN is a polar organic solvent with very high dielectric constant and the polarity index of 5.8, it tends to dissolve the reactants to enhance yield. To further improve the desired yield, we replaced H 2 O 2 with organic peroxide (TBHP) which enhances proper substrate mixing . With TBHP (0.1 mL) in MeCN the yield of selective oxidation drastically increases to 85% within 6 h (Table , entry 7).…”
Section: Resultsmentioning
confidence: 99%
“…To further improve the desired yield, we replaced H 2 O 2 with organic peroxide (TBHP) which enhances proper substrate mixing. [48] With TBHP (0.1 mL) in MeCN the yield of selective oxidation drastically increases to 85% within 6 h ( [12][13], no significant conversion occurred. Whereas, when the reaction was performed without a catalyst or an oxidant traces of the product could be found indicating that oxidation proceeds only in the presence of a metal catalyst and an oxidant ( Table 1, entries [14][15].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies were reported on the syntheses of BzAld and BzAcid via partial oxidation of benzyl alcohol over heterogeneous catalysts based on copper (CuHC), which is an earth‐abundant, relatively cheap transition metal capable of conferring versatile catalytic properties to materials for organic reactions involving one or two‐electron mechanisms, explaining why it is one of the most utilized transition metals in synthetic chemistry . CuHC reported for BzOH conversion were mainly copper organocomplexes or copper nanoparticles supported on (organofunctionalized) silica or clay . Alternative to supported catalysts, bulk catalysts may offer framework metal site isolation and uniform metal distributions, and, consequently, enhance the catalyst usage.…”
Section: Introductionmentioning
confidence: 99%